Editorial. Issue 8 (August 2021) - Mansfield-Devine, Steve
Abstract : It's not often I get to write about defrocked priests. And now my chance is here, it turns out not to be an opportunity to indulge in some gleeful yellow journalism. Instead, it's a cautionary tale about the evils of peddling data.